PELAPISAN LILIN SEBAGAI UPAYA UNTUK MEMPERTAHANKAN KUALITAS BUAH SALAK Malacca edulis Reinw) BALI = BEESWAX COATING TO MAINTAIN QUALITY OF SNAKE FRUIT OF BALI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
This research was conducted to determine the deterioration types of snake fruit of Bali after harvesting, and to determine the effect of beeswax coating on the quality of snake fruit of Bali during storage in the bamboo box at 22Â° - 26Â°C, and 70 - 75 % RH. The parameters of deterioration types such as weight loss or moiture content was determined every day, while pH, organic acid, vitamin C, sugar, tannin, texture, and total plate count for fungi were determined every 4 days until 12 days storage. Visual observation showed that the deterioration types of snake fruit of Bali after harvesting were injuries, bruising, browning, wilting, drying out, infected by fungi, and decay, respectively. These deteriorations were mainly caused by mechanical, physiological, microbiological, and biological factors and also delaying in harvesting. Beeswax coating was significantly able to maintain vitamin C, tannin, organic acid content and pH of fruits during handling and storage, and it was able to extend storage life from 7 days to 12 days. Water loss, weight loss, and sugar degradation were inhibited, but microbiological decay and loss of firmness or texture were still occur. The best quality of snake fruit of Bali and the longest storage life (12 days) were obtained from the beeswax coating at 10 % concentration.